From digital pricing to digital marketing and digital distribution - KARAOULANIS, ANDREAS (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Contemporary digital markets tend to be different in several ways from the traditional ones. In this short paper the author tries to explain the main lines upon which contemporary companies try to implement their digital pricing, digital marketing, and digital distribution.